2018
DOI: 10.1101/280750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Causal evidence for mnemonic metacognition in human precuneus

Abstract: Metacognition is the capacity to introspectively monitor and control 31 one's own cognitive processes. Previous anatomical and functional neuroimaging 32 findings implicated the important role of precuneus in metacognition processing, 33 especially during mnemonic tasks. However, the issue of whether this medial parietal 34 cortex is a domain-specific region that supports mnemonic metacognition remains 35 controversial. Here, we focally disrupted this parietal area with repetitive transcranial 36 magneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Fleming et al 55 , for example, found evidence that individuals with anterior prefrontal cortex lesions, which performed two metacognitive tasks in two different domains (memory vs. perception), showed only a deficit in perceptual metacognition. In this vein, Ye et al 56 investigate the role of the medial parietal cortex (precuneus) in the metacognitive capacity of individuals in memory tasks and visual perception. Interestingly, the disruption of activity through transcranial magnetic stimulation (TMS) only negatively impacts metacognitive efficiency on memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Fleming et al 55 , for example, found evidence that individuals with anterior prefrontal cortex lesions, which performed two metacognitive tasks in two different domains (memory vs. perception), showed only a deficit in perceptual metacognition. In this vein, Ye et al 56 investigate the role of the medial parietal cortex (precuneus) in the metacognitive capacity of individuals in memory tasks and visual perception. Interestingly, the disruption of activity through transcranial magnetic stimulation (TMS) only negatively impacts metacognitive efficiency on memory tasks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the meta-analysis on accuracy measures failed to reveal a main effect or interaction with the cortical region that was targeted or the memory process that was stimulated, based on the systematic review of the published studies, it seemed to be the case that several studies found that applying rTMS to regions of parietal cortex affected the subjective experience of remembering as evidenced by modulation of confidence ratings even in the absence of effects on objective measures of accuracy. For example, Ye et al (2018) recorded participants playing an action-adventure video game and then applied offline 1 Hz rTMS at 110% AMT to the precuneus prior to snapshot images from the video game and then tested subjects' temporal order memory and confidence ratings. The authors found decreases in confidence ratings during retrieval following precuneus compared to vertex stimulation, despite no differences in memory performance (Ye et al, 2018).…”
Section: Limitations Of Conducting a Meta-analysis On Available Rtms mentioning
confidence: 99%
“…For example, Ye et al (2018) recorded participants playing an action-adventure video game and then applied offline 1 Hz rTMS at 110% AMT to the precuneus prior to snapshot images from the video game and then tested subjects' temporal order memory and confidence ratings. The authors found decreases in confidence ratings during retrieval following precuneus compared to vertex stimulation, despite no differences in memory performance (Ye et al, 2018).…”
Section: Limitations Of Conducting a Meta-analysis On Available Rtms mentioning
confidence: 99%
“…2. The brain not only infers mental spaces (Haun & Tononi, 2019;O'Reilly et al, 2017;Utevsky et al, 2014;Williford et al, 2018;Ye et al, 2018), but it populates these spaces with representations of sensations and actions, so providing a basis for causal reasoning and planning via mental simulations. 3.…”
mentioning
confidence: 99%